Relationships Between Deprivation and the Self-Reported Health of Older People in Northern Ireland. (June 2017) - Doebler, Stefanie; Glasgow, Nina
Objective: There are few studies on relationships between deprivation and the self-reported health of people aged above 64 years, and no studies fully representative of Northern Ireland's older population. This article addresses this gap.Method: Deprivation of older people as reported in the 2001 and 2011 Censuses and the relationship with self-reported health are analyzed over a 10-year span using multilevel modeling. The data are from the Northern Ireland Longitudinal Study (NILS) linked to 2001-2011 Census returns. Deprivation measures include housing tenure; property value; access to a car; and educational, employment, and area-level income deprivation.Results: Older people suffering deprivation face a significant health disadvantage over a 10-year time span.Discussion: This health disadvantage is stronger in men than in women, likely due to conservative gender roles that are prevalent among Northern Ireland's older population, leading to psychological distress especially among deprived men. The analysis found strongly significant area-level effects, aggravating the health impact of deprivation.